Eu corporate law and eu comapny tax law - Cerioni, Luca (Edward Elgar, 2007)
The book illustrates the key developments in EU corporate law and EU company tax law, the EU planned initiatives in these areas, and - at a time when member states increasingly tend to use company law and company tax provisions to attract businesses and investments - it suggests how future developments can contribute to the undistorted functioning of the internal market and to the strategic `Lisbon-objective'.